PENGARUH MOTIVASI BELAJAR DAN SARANA PRASARANA PENDIDIKAN TERHADAP PRESTASI BELAJAR TARUNA TEKNIK PENERBANGAN PADA SEKOLAH TINGGI PENERBANGAN INDONESIA - Yayuk Suprihartini (Politeknik Penerbangan Indonesia Curug, 2018)
The purpose of research to known and analysed the effect of learning motivation and education infrastructure individually as well as collectively equal to the learning achievement of STPI cadets. The method used is quantitative method, with samples value 74 respondents from a population of 284 cadets, through the questionnaire data collection techniques. Then analyzed test of T and F, the correlation coefficient, determination, regression, path analysis. Research results correlation motivation toward learning achievement expressed strong cadets at 0.671 and the contribution value of 31.6%. Correlation means education infrastructure on the learning achievement of cadets at 0.639 expressed strong with contribution value of 25.8%. The Effect of learning motivation and education infrastructure jointly to the learning achievement of cadets at 0.758 have expressed strong with contribution value of 57.4% while the remaining 42.6% influenced by other factors. In outline the results of this study can be concluded that the learning achievement of STPI cadets be improved through increased motivation to learn and education infrastructure